A Consideration Set Model sebagai Model Pemahaman Konsep Switching Behavior pada Produk Handphone - Rachmawati, Veronika (Jurnal Widya Manajemen & Akuntansi, 2005)
This research focused of consideration set to switch brands in sellular phone purchase. Research model same as with sambandam & Lord (1995) and using sellular phone for research object. The result show that the replicated research model could be supported as the researchers expected. Seven of the eleven hypotheses, have been supported, while the others have not. This condition indicates that consideration sets are shown to affect the switching decision both directly and indirectly (motivating retailer search activities). For further research are needed to considered other factors which hove not been revealed were found as desire to have newly sellular phone, a desire to try other brands (variety seeking), and boredom of the owned sellular phone.